Electrical high-frequency stimulation of the human thoracolumbar fascia evokes long-term potentiation-like pain amplification - Schilder, Andreas; Magerl, Walter; Hoheisel, Ulrich; Klein, Thomas; Treede, Rolf-Detlef (Pain, 2016)
Nociceptive long-term potentiation, a use dependent increase in synaptic efficacy in the dorsal horn of the spinal cord is thought to contribute to the development of persistent pain states. So far, no study has analyzed the effects of high-frequency stimulation (HFS) of afferents from deep tissues (muscle and fascia) on pain perception in the back in humans. In 16 healthy volunteers, the multifidus muscle and the overlying thoracolumbar fascia were stimulated with electrical high-frequency pulses (5 × 100 pulses at 100 Hz) through bipolar concentric needle electrodes placed at lumbar level (L3/L4). Electrical pain thresholds were lower (P < 0.001) and pain ratings were higher for fascia compared with muscle stimulation (P < 0.05). For both tissues, pain ratings increased significantly across the five 100 Hz trains (from 15 to 22 numerical rating scale for fascia, from 8 to 12 numerical rating scale for muscle; both P < 0.01). Fascia HFS increased fascia pain ratings 2.17 times compared with the unconditioned control site (P < 0.001), but had no significant effect on pain sensitivity of the muscle. The HFS in muscle had no significant effect on muscle pain, but decreased pain sensitivity of the overlying fascia by 20% (P < 0.05). In additional experiments using the same electrodes and followed over >60 minutes post-HFS, potentiation by fascia HFS was similar to that of skin HFS. These findings show that the spinal input from the fascia can induce long-term changes in pain sensitivity for at least 60 minutes making it a candidate potentially contributing to nonspecific low back pain.